Impact of work-family support on job burnout among primary health workers and the mediating role of career identity: A cross-sectional study - Yang, Diling; Fang, Guixia; Fu, Danmin; Hong, Mengyuan; Wang, Haoyu; Chen, Yuqing; Ma, Qinglian; Yang, Jinxia (Frontiers in Public Health, 2023)
Objective: In China, medical workers in the primary sector shoulder the task of providing people with the basic medical and public health services, and are the “gatekeepers” of the public health. This study aims to analyze the current situation of job burnout among primary health workers of China, and shed light on the effect of work-family support and career identity on job burnout among them and their relationships. This may provide a new perspective for primary health care institutions and health administrative departments so as to formulate policies to “attract, retain and stabilize” primary health workers. Methods：A multi-stage sampling method was adopted to select 8,135 primary health workers from 320 primary health care institutions in a province of central China. A descriptive statistical analysis, univariate analysis, Pearson correlation analysis, and mediation effect analysis were applied to analyze the effects of work-family support and career identity on job burnout among primary health workers as well as the mediating role of career identity. Results: Among 8,135 primary health workers, 4,911 (60.4%) participants had mild to moderate levels of job burnout, 181 (2.2%) participants had severe job burnout, and the burnout detection rate is 62.6%. Work-family support was negatively correlated with job burnout (r=-0.46, p<0.01) and positively correlated with career identity (r=0.42, p<0.01). Work-family support (β=-0.346, p<0.01) and career identity (β=-0.574, p<0.01) were negative predictors of job burnout respectively. In addition, career identity had a mediating effect between work-family support and job burnout, with the mediating effect contributing 33.7% to the overall effect. Conclusions: The findings of this study demonstrate that work-family support is a protective factor against job burnout in primary health workers and reveal that career identity is a critical mediating mechanism linking work-family support to burnout. We propose to reduce job burnout by strengthening work-family support (especially work support), enhancing career identity, increasing the number of primary health workers and reducing the workload of existing incumbents, which can provide important practical implications for the future prevention and intervention programs.